2016
DOI: 10.1007/s10265-015-0776-x
|View full text |Cite
|
Sign up to set email alerts
|

Lead tolerance mechanism in Conyza canadensis: subcellular distribution, ultrastructure, antioxidative defense system, and phytochelatins

Abstract: We used hydroponic experiments to examine the effects of different concentrations of lead (Pb) on the performance of the Pb-tolerable plant Conyza canadensis. In these experiments, most of the Pb was accumulated in the roots; there was very little Pb accumulated in stems and leaves. C. canadensis is able to take up significant amounts of Pb whilst greatly restricting its transportation to specific parts of the aboveground biomass. High Pb concentrations inhibited plant growth, increased membrane permeability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Our findings corroborated with the study carried out by Li, et al . 112 who reported enhancement in amino acids content in response to 24-EBL application. Similarly, application of SA resulted in elevation in levels of amino acids specifically proline, glycine betaine and glutathione in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings corroborated with the study carried out by Li, et al . 112 who reported enhancement in amino acids content in response to 24-EBL application. Similarly, application of SA resulted in elevation in levels of amino acids specifically proline, glycine betaine and glutathione in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The frozen plant fresh leaves (1 g) were homogenized and the subcellular fractions were separated according to Su et al (2014) and Li et al (2016). Each plant sample was homogenized in 12-ml precooled extraction buffer containing 250 mmol/L sugar, 50 mmol/L Tris-HCl (pH 7.5), 1 mmol/L MgCl 2 , and 10 mmol/L cysteine using a chilled mortar and pestle.…”
Section: Cell Wall Organelle and Vacuole Isolationmentioning
confidence: 99%
“…Copper (Cu) bound to the cell walls in fibrous roots of Malus sieversii mainly exists in phosphate and oxalate forms, which can explain some of the variation in Cu sensitivity in M. sieversii (Wang et al, 2016). Recently, Li et al (2016) reported that the cell walls and intercellular spaces are the main location of Pb accumulation in the roots of Conyza canadensis . The cell walls restrict Pb uptake into plant roots and act as an important barrier to protect root cells (Wang Y. et al, 2015).…”
Section: Introductionmentioning
confidence: 99%